Learning Media Design of Introduction à la Civilisation Française Using Augmented Reality Technology Through Instagram Platform - Prasetyo, Alzihra Jasmin; Hardini, Tri Indri; Gumilar, Dudung (Edunesia : Jurnal Ilmiah Pendidikan, 2025)
This study aims to describe the design of microblog learning media supported by augmented reality-based interactive quiz filters through the Instagram platform for humanities courses, especially Civilisation Française. The research methods used are descriptive qualitative with a Design and Development (D&D) approach. Designing learning media products involves planning, production, and evaluation. The research findings show that (1) based on the material aspect, the learning media product through the Instagram platform is very feasible to use, with a product feasibility percentage result of 94%, and (2) based on the media aspect, the learning media product through the Instagram platform is very feasible to use with a product feasibility percentage result of 100%. These results indicate that the material and media aspects of the designed product have quality content, appropriate learning objectives, attractive appearance design, ease of use and accessibility. This research produces a product that is very feasible to use in learning Civilisation Française. The microblog and augmented reality-based interactive quiz filter can be accessed via mobile phone on the Instagram account @apprendrecf.